Pengembangan Media Pembelajaran Interaktif Berbasis Lumio Untuk Meningkatkan Motivasi Belajar Siswa - Saatiah, Saatiah; Ahyar, Ahyar; Fitrianingsih, Nur (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2025)
This study aims to develop interactive learning media based on Lumio to incress the learning motivation of class X film students at SMK Negeri 1 Bolo. Limited infrastucture and conventional learning methods that are not in accordance with the characteristics of the digital generation are the bacghround of the research. The method used is research and development (R&D) with the ADDIE model which includes analysis, design, development, implementation, and evaluation. Data collection was done though observation, interviews, expet validation, and students questionnaires. The result showed that Lumio learning media was declared very feasible to use based on the validation of media and materialexperts, and effective in increasing student learning motivation. Lumio offers attractive visual displays and interactive features that require active student participation, creating a fun learning atmosphere. This research recommends integrating the use of interactive technology in learning practices to improve the quality of 21 st centuty education.Kata kunci: Lumio, Media Pembelajaran, Motivasi Siswa